Nilai Perjuangan pada Novel Sisi Tergelap Surga Karya Brian Khrisna : Kajian Sosiologi Sastra - Dewi Putri Nafila; Ahmad Ilzamul Hikam (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
This study aims to reveal the value of struggle in the novel The Darkest Side of Heaven by Brian Khrisna through a sociological literary approach. This novel reflects the lives of lower-class people in Jakarta who live under social, economic, and cultural pressures. This study uses a qualitative descriptive method with a literature study approach. Data are analyzed based on the content of the text that describes the values of the struggle of the characters in the novel. The results of the study show that there are two main values of struggle, namely the value of being willing to sacrifice and the value of never giving up. The value of being willing to sacrifice is reflected in characters such as Sobirin, Juleha, Kuncahyo, and a father who is willing to put aside self-esteem, comfort, and personal needs for the sake of his family. Meanwhile, the value of never giving up is seen from Juleha and Tomi's persistence in facing poverty, as well as Kuncahyo's spirit who continues to work hard even in inhumane conditions. This novel illustrates that the struggle of marginalized people is not only about survival, but also shows strong social values, such as love, sacrifice, solidarity, and optimism. This study confirms that literature functions as a mirror of social reality and a means to foster empathy and social awareness towards the lives of marginalized communities in big cities.